Review Literature about Influence of Prayer and Dhikr in Improving Mental Health Based on the Qur'an Surah Ar-Ra'd Verse 28 - Muhammad Nor (Bulletin of Islamic Research, 2023)
This article discusses the influence of prayer and dhikr in improving mental health based on the Qur'an Surah Ar-Ra'd verse 28. This verse describes the peace that can be achieved by believers by remembering Allah. This study aims to explore how prayer and dhikr can be a tool to improve psychological well-being, reduce stress, and improve the emotional balance of individuals. The methods used in this study is studies Qualitative . The results of this study indicate that prayer and dhikr have a positive effect on reducing anxiety, depression, and increasing feelings of peace and satisfaction. It is recommended that individuals experiencing mental health problems can integrate prayer and dhikr into their daily lives as an easily accessible and effective form of therapy.